Certification by levels in the fight against corruption. The case of the Supervisory Body for Public Procurement (OSCE) - Huamán Ordóñez, Luis Alberto (2023)
The author of this essay focuses on administrative certification as an administrative law technique and points out that the intentional notion of such administrative act is a concept that does not allow the understanding of the analyzed issue. To this end, it is taken into account that the certification does not imply a mere administrative intentional declaration, but involves statements that prove sense of judgment, desire and knowledge of public organization in order to then analyze the role of procurement as a singular area of legaladministrative relations in which public authorities interact with individuals, being analyzed in a role different from the elementary one of administered subjects, so that both parties obtain a mutual benefit under the enormous legal administrative regime which, although intervenes as a contracting party, it does not lose its capacity as a public administration entity. Thus, with the use of hermeneutic and historical techniques, this research shows that certification by levels in the field of public procurement is an interesting technical tool to reduce the lack of experience of those in charge of the various procurement procedures and to discourage behaviors that tend to take advantage of the absence of specialized training.